Characterization of the oral virome in patients with diabetes mellitus - Zhang, Yidi; Zhang, Yue; Xing, Guorui; Mei, Ting; Wang, Minhui; Huang, Chunxia; Yi, Hanzhi; Zhan, Yu; Yang, Sen; Yan, Qiulong; Li, Shenghui; Chen, Changming (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionDiabetes mellitus (DM), a globally prevalent chronic metabolic disorder characterized by persistent hyperglycemia, has been increasingly linked to dysbiosis of the oral microbiome. However, the relationship between the virome, a crucial component of the oral microbiome, and DM remains poorly understood.MethodsTo explore the characteristics of the oral virome in DM patients, we analyze the oral viral communities of 45 DM patients and 40 healthy controls (HC) using a publicly available metagenomic dataset.ResultsOur analysis revealed no significant differences in a-diversity between DM patients and HC. However, Podovirus was enriched in DM patients, whereas Microviridae was more prevalent in HC. A total of 1,131 virus signal was identified, primarily belonging to the Siphovirus and Myovirus taxa. Notably, HC-enriched vOTUs exhibited broader host tropism, predominantly infecting Prevotella, Fusobacterium, and Gemella, whereas DM-enriched vOTUs showed narrower specificity for Pauljensenia and Veillonella. Cross-kingdom network analysis suggested that certain viruses (HMP_1157.k81_309051) may have potential links to the development of DM, and the bacteria genus F0040 might play a significant role in maintaining oral health. Additionally, the random forest model based on viral markers effectively distinguished between HC and DM patients (AUC =90.8%), significantly outperforming the bacterial model.DiscussionThis indicates that these unique viral markers could serve as potential targets for DM intervention. Taken together, our findings reveal distinct alterations in the oral virome of DM patients and highlight its promise as a novel diagnostic and therapeutic target in metabolic disease research.